9z-6+7z=16-6

Simple and best practice solution for 9z-6+7z=16-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9z-6+7z=16-6 equation:



9z-6+7z=16-6
We move all terms to the left:
9z-6+7z-(16-6)=0
We add all the numbers together, and all the variables
9z+7z-6-10=0
We add all the numbers together, and all the variables
16z-16=0
We move all terms containing z to the left, all other terms to the right
16z=16
z=16/16
z=1

See similar equations:

| x+12=4x-39 | | 7g+3g-10+3=43. | | 3(4547-y)+4y=17441 | | 7+17f-8=11+11f | | 7(y+4)=-2(8y-8)+5y | | -17+v-20=-3+11 | | 45=16v-7v | | 1x+8=3x+4 | | -12t+20+3t=-20+t | | 14-8x=4x-46 | | 20-4y=-7-y+18 | | 40x+1.5x=1250 | | 3c^2-375=0 | | -7(x-1)-(-8x-8)=-2 | | 5c+7=3c-5 | | 3a+9=7a+5 | | 63+2x=105 | | 3(2x-3)=5(x+5) | | 2/3(y-18)=7 | | 7m=9+4m | | 63=2x=105 | | x-3/5=5 | | 2b+1=5b+10b= | | -9=-5-3a-11 | | a=15=4a-3 | | 7g-8=10g+8-4g | | -4(a+6)=-63 | | -6.5+1.3x=9.1 | | 3y+2=8y+17 | | h/2+h/3=6 | | 7r-8=6r | | 5(3x-8)=-115 |

Equations solver categories